PENGARUH KUALITAS PRODUK, HARGA DAN CTRA MEREK TERHADAP KEPUASAN PELANGGAN DENGAN LOYALITAS PELANGGAN SEBAGAI VARIABEL INTERVENING MIXUE ICE CREAM & TEA DI SITUBONDO - Yusfan Ferdiansyah; Ika Wahyuni; Lita Permata Sari (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Currently, the growth of the Indonesian food and beverage industry is underpinned by strong competencies. The development of ice cream products in Indonesia is ongoing in many regions. This indicates a growing variety of ice cream products available, both imported and domestically produced. The development of ice cream products creates intense competition, so each new product improves its quality, potentially reducing consumer demand. The purpose of this study is to determine the effect of product quality, price and brand image on customer satisfaction with customer loyalty as an intervening variable Mixue Ice Cream & Tea in Situbondo. The sampling technique in this study used a random sampling technique, with 98 respondents. Data analysis and hypothesis testing used Structural Equation Analysis - Partial Least Square (PLS-SEM). The results of hypothesis testing using the Smart PLS 3.0 application, show that product quality has a positive and significant effect on customer loyalty, price has a positive but not significant effect on customer loyalty, brand image has a positive and significant effect on customer loyalty, product quality has a positive but not significant effect on customer satisfaction, price has a positive but not significant effect on customer satisfaction, brand image has a positive but not significant effect on customer satisfaction, customer loyalty has a positive and significant effect on customer satisfaction, product quality has a positive and significant effect on customer satisfaction through customer loyalty, price has a positive but not significant effect on customer satisfaction through customer loyalty, brand image has a positive and significant effect on customer satisfaction through customer loyalty.